A Fixed Point Theorem for L-Contraction in Generalized D-Metric Spaces (Baghdad Science Journal, 2025)
We define L-contraction mapping in the setting of D-metric spaces analogous to L-contraction mappings [1] in complete metric spaces. Also, give a definition for general D- matric spaces.And then prove the existence of fixed point for more general class of mappings in generalized D-metric spaces.